THE INFLUENCE OF LEADERSHIP AND STRATEGIC PLANNING TOWARD LOCAL REVENUE (AT WEST BANDUNG REGENCY) - Biller Panjaitan; Ony Djogo (JEES: Journal of Economic Empowerment Strategy, 2019)
The goal of this research is to describe the influence of leaderships and strategic planning toward local revenue at West Bandung Regency. Research method is Quantative research and collect data by quessioner, interview, observation and documentation. The variables were leaderships and strategic planning. as the independent variables, the dependent variable was local revenue. Data have been analyzed through (Multiple Regresion). The result of this research showed that leaderships and strategic planning. influence the local revenue The influence of leaderships and strategic planning toward local revenue is positive it means that the more higher leaderships and the strategic planning the more higher local revenue and it has mean in real rank p < 0.01. By this research, the hypothesis, which has been proposed, leaderships and strategic planning will influence local revenue. The result has showed that the mean of local revenue is 0. 4570 or the grade variation of local revenue is 45,70 percent depending on leaderships and strategic planning.